GAS FLOW CONTROL SYSTEM IN REACTIVE MAGNETRON SPUTTERING TECHNOLOGY - I. M. Klimovich; V. N. Kuleshov; V. A. Zaikou; A. P. Burmakou; F. F. Komarov; O. R. Ludchik (Приборы и методы измерений, 2015)
It is known that the discharge parameters and the chemical composition of the particles flux impinging onto the substrate during a reactive magnetron sputtering are unstable. As a result spontaneous transitions between the «metal» mode of the target surface and the «poisoned» mode of the target surface have been observed. This leads to nonrepeatability of the coating compositions from process to process. The aim of this work is to design a gas flow control system for reactive sputtering processes. The control system allows to maintain a steady nonequilibrium state of the magnetron discharge in transition mode where the chemical state of the target surface is unstable. The intensities of spectral lines of the discharge spectrum are proposed as control parameters. Photodiode detectors were used for registration of intensities of spectral lines. A gas flow control system regulates argon and reactive gas flow automatically, using feedback signals from photodiode detectors on the intensities of the spectral lines, vacuum gauge, ion current sensor, sensors of discharge current and voltage. As an example, the process of reactive magnetron Ti-Al-N deposition is considered. The following discharge parameters are controlled during sputtering a composite target based on Ti with Al cylindrical inserts: current, voltage, total pressure of a gas mixture, substrate temperature, bias voltage and current of the substrate. Nitrogen flow was controlled by the spectral line intensity of titanium TiI 506,5 nm. The value of the line intensity is connected with the value of reactivity. Elemental composition and structure of the Ti-Al-N coatings were studied using Rutherford backscattering spectroscopy, scanning electron microscopy and X-ray diffraction. It was found, that stoichiometric Ti-Al-N coatings have a globular structure, enhanced hardness and low friction coefficient in contrast to Ti-Al-N coatings with nonstoichiometric composition, which have a columnar structure. As result, it was shown, that a gas flow control system allows to control stoichiometry composition and physical properties of the deposited coating.